ICT IMPLEMENTATION TO THE EDUCATION OF APPLIED MATHEMATICS - VAGASKA, Alena (Trends in education, 2009)
The author of the paper deals with the problems of applied mathematics teaching at technical universities. Emphasizing the effectiveness of technical education at universities and applicative character of mathematical disciplines, the paper presents the implementation of ICT as well as technical applications to the teaching of applied mathematics in the context of innovative approach to the teaching.
Keywords: applied mathematics; ICT; numerical methods; approximation; MS Excel